STUDI KASUS TENTANG SMARTPHONE DI KALANGAN ANAK-ANAK - Irma yanti; Lucy Pujasari Supratman (Dialektika, 2019)
Based on data from the Association of internet Service Providers in Indonesia (APJII, 2017) internet users in Indonesia in 2017 amounted to 143.26 million people, meaning of the total population of Indonesia of 262 million people, including 54, 68% are active Internet users. UNICEF explains that 30 million children and teenagers use the internet and digital media as the most important communication channel. This research wants to explain how smartphone usage by children from elementary school students in SDN Puntangsari. This research uses qualitative method with explanatory case study approach. This research has been going on for one year and the informans who are involved are 29 informants. The research results found, Informan access the internet 2- 3 hours per day, the informants are skilled in using many features on their smartphones, such us: Social Media, Google, You tube, games, photos / video editors, music, Share it, and Translated. They understand smartphone usage and how do it work. Informans use smartphone for education, communication, entertainment, social, and get information. Conclusion, informans have ability and understanding how smartphone usage which are appied in everyday life.